Clinical Pattern and Management of Acute Pancreatitis Our Experience (Journal of Bangladesh College of Physicians and Surgeons, 2014)
Background: Acute pancreatitis (AP) is an acute inflammatory condition of the pancreas that may extend to local and distant extrapancreatic tissues. It is a life threatening disease that has many causes, few effective treatments, numerous serious complications, and an often unpredictable course. The objectives of this study are to develop our knowledge about presentation and diagnosis of acute pancreatitis, to assess the patient with acute pancreatitis accurately and to develop a standard management protocol. Methods: This observational study was carried out in Combined Military Hospital (CMH) Dhaka, CMH Momenshahi and CMH Ghatail during the period of June 2007 to December 2010. A total 25 patients of Acute Pancreatitis were studied retrospectively, evaluated and managed.Results: In this study 25 patients 19 (76%) were male (male : female = 3.17:1), age range 08 to 55 years, Mean age 38.92 years. Maximum number of the patients fall into fourth and fifth decades. All patients presented with abdominal pain, specially in upper abdomen. Laboratory test revealed leucocytosis and high serum and urinary amylase, positive findings in Ultrasonogram and CT scan found in all patients. Gall stone was the leading cause 14 (56%). 20 (80%) patient developed some form of complications. 24 patients were treated conservatively. Average hospital stay was 15.52 days. Serious regional and systemic involvement in Acute Pancreatitis causes multiple organ or system failure. Conclusion: Early diagnosis and effective treatment can significantly reduce the morality and morbidity. DOI: http://dx.doi.org/10.3329/jbcps.v31i3.20977 J Bangladesh Coll Phys Surg 2013; 31: 122-127